Computed Tomography-Driven Design and Fused Filament Fabrication of Graded Density Bone Scaffolds - Luca Grigolato; Gianpaolo Savio (Applied Sciences)
The design of scaffolds and prostheses benefits from the opportunities provided by additive manufacturing technologies. Specifically, scaffold design using cellular structures based on lattices has become a significant focus. These lattice-based scaffolds exhibit intricate and complex shapes with controlled macro-porosity. In this study, a method is presented that enables the modeling of a graded-density lattice structure for material extrusion additive manufacturing, without relying on a geometric lattice model. The methodology utilizes computed tomography (CT) scans as inputs to obtaining a 3D scalar field and a surface model. The lattice structure is designed and generated within the computer-aided manufacturing (CAM) software, ensuring consistent machine toolpaths. The 3D scalar field, representing a relative density map derived from CT Hounsfield units, drives the variation of the extrusion parameters generated by the CAM, achieving a graded-density lattice. To demonstrate the effectiveness of the method, a section of a human femur bone with a lattice with a triply periodic minimal surface (TPMS) gyroid pattern was designed and 3D-printed, replicating the relative density of the target tissue.